Padat Populasi Wereng Batang Coklat (Nilaparvata lugens) dan Wereng Hijau (Nephotettix virescens ) pada Tanaman Padi Varietas Inpara 2 di Kampung Bokem Kabupaten Merauke Papua - Jefri Ando Sembiring; Johanna A Mendes (Universitas PGRI Palembang, 2022)
The purpose of this study was to analyze the population density and intensity of attack of Brown Planthopper (Nilaparvata lugens Stall) and green leafhoppers (Nephotettix virescens) on rice plants of Inpara 2 variety in Bokem Village. The research was conducted from August to October 2022 in the rice fields of Bokem Village, Merauke District. Sampling was carried out on three rice fields with an area of 20 x 40 m divided by five observation sub-plots spread diagonally with a size of 2 x 2 meters. Plant height of Inpara 2 variety at the age of 14 DAP (23.1 cm), 28 DAP (33.2 cm), 42 DAP (53.8 cm), 56 DAP (64 cm) and 70 DAP (70.2 cm) . The number of tillers at the age of 14 days old (3.2 tillers), 28 days old (5.5 tillers), 42 days old (11 tillers) and 56 days old (12.1 tillers). The panicle length of the Inpara 2 rice variety was on average (21.1 cm) while the weight of 1000 grains was 14.7 grams. Brown planthopper population at the age of 14 days after planting (0.19 individuals), 28 days after birth (0.07 individuals), 42 days after birth (0.19 individuals) and 56 days after planting (0.31 individuals) while the green leafhopper population at 14 days old (0.30 individuals) 32 individuals), 28 days old (0.33 individuals), 42 days old (0.25 individuals) and 56 days old (0.01 individuals).Â Keywords: Pest, Inpara 2, Population,Â Brown planthopper, green leafhoppers